Pengaruh Kompetensi Kerja, Pelatihan Kerja, dan Pengembangan Karier Terhadap Kinerja Karyawan Divisi Teknologi pada PT Digdaya Olah Teknologi Indonesia di Kota Malang - Dion Silvia Adi Saputra; Sumiati Sumiati (STIKes Ibnu Sina Ajibarang, 2024)
PT Digdaya Olah Teknologi Indonesia is a company engaged in technology and domiciled in the city of Malang. PT Digdaya Teknologi Indonesia focuses on technology development solutions that have a significant role in various sectors, including MSMEs, private companies, and the government sector. This study aims to prove and analyze the influence of work competence, job training, and career development on the performance of employees of the technology division of PT Digdaya Olah Teknologi Indonesia in Malang. The research method used was quantitative with a saturated sampling technique on 54 employees of the technology division of PT Digdaya Olah Teknologi Indonesia. The analysis technique used in this study is multiple linear regression analysis. Some of the analyses used in this study are, Descriptive Analysis, Validity Test, Reliability Test, Correlation Coefficient Analysis, Partial Hypothesis Test, Simultaneous Hypothesis Test, and Determination Coefficient Test. Meanwhile, the classical assumption tests used in the study are the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Linearity Test, Autocorrelation Test. The results of this study show that work competence has a significant effect on the performance of employees of the technology division of PT Digdaya Olah Teknologi Indonesia in Malang city, job training has a significant effect on the performance of employees of the technology division of PT Digdaya Olah Teknologi in Malang city, career development has a significant effect on the performance of employees of the technology division of PT Digdaya Olah Teknologi in Malang city. And based on the results of the analysis, it was explained that work competence, job training, and career development simultaneously affected employee performance by 53.6% while the remaining 46.4% was influenced by other variables that were not studied in this study.